Penerapan Spatial Durbin Model (SDM) untuk Menganalisis Faktor-Faktor yang Mempengaruhi Persentase Penduduk Miskin di Kabupaten Cianjur Tahun 2021 - Raspati, Rifqy Sayidi; Herrhyanto, Nar; Agustina, Fitriani (Jurnal EurekaMatika, 2024)
In this research, we built a regression model to analyze the factors influencing the percentage of poor people in Cianjur Regency. The method used to model the problem of the percentage of poor people is Durbin spatial regression analysis by considering location aspects of both the dependent variable and the independent variable. Of the six independent variables taken, only four independent variables can be modeled using Durbin spatial regression. This is caused by the results of the Moran Index Test which states that there is spatial autocorrelation in these four variables. Based on Durbin's spatial regression analysis, the results showed that the variables that significantly influenced the percentage of poor people in Cianjur Regency in 2021 were the average length of schooling and life expectancy at birth. A high average number of years of schooling and life expectancy at birth can reduce the percentage of poor people in Cianjur Regency.Keywords: Moran's Index Test, Percentage of Poor People, Spatial Durbin Regression. AbstrakPada penelitian ini dibangun model regresi untuk menganalisa faktor-faktor mempengaruhi persentase penduduk miskin di Kabupaten Cianjur. Metode yang digunakan untuk memodelkan masalah persentase penduduk miskin tersebut adalah analisis regresi spasial Durbin dengan mempertimbangkan aspek lokasi baik dari variabel dependen dan variabel independen. Dari enam variabel independen yang diambil hanya empat variabel independen yang dapat dimodelkan menggunakan regresi spasial Durbin. Hal tersebut disebabkan oleh hasil Uji Indeks Moran yang menyatakan terdapat autokorelasi spasial pada empat variabel tersebut. Berdasarkan analisis regresi spasial Durbin didapatkan hasil bahwa variabel yang berpengaruh secara signifikan terhadap persentase penduduk miskin di Kabupaten Cianjur Tahun 2021 adalah rata-rata lama sekolah dan usia harapan hidup saat lahir. Nilai rata-rata lama sekolah dan usia harapan hidup saat lahir yang tinggi dapat menurunkan persentase penduduk miskin di Kabupaten Cianjur.